2017
DOI: 10.1088/1741-2552/aa5847
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised frequency-recognition method of SSVEPs using a filter bank implementation of binary subband CCA

Abstract: The statistical test shows that the proposed unsupervised method significantly improves the performance of the SSVEP-based BCI. It can be usable in real world applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…The accuracy of the CCA of the 4 s TW was 88.58%. Islam et al [43] reported that under the CCA-based method, the average accuracy of 10 subjects with 4 s TW for 12 stimuli reached about 93%, which was higher than the accuracy of this study. Chen et al [44] reported that under the four stimuli, the CCA-based method had reached 62% accuracy with a 4 s TW for nine subjects.…”
Section: Discussioncontrasting
confidence: 83%
“…The accuracy of the CCA of the 4 s TW was 88.58%. Islam et al [43] reported that under the CCA-based method, the average accuracy of 10 subjects with 4 s TW for 12 stimuli reached about 93%, which was higher than the accuracy of this study. Chen et al [44] reported that under the four stimuli, the CCA-based method had reached 62% accuracy with a 4 s TW for nine subjects.…”
Section: Discussioncontrasting
confidence: 83%
“…The CCA algorithm is improved based on the characteristics of the EEG evoked by this paradigm, which is used in training scenarios. The algorithm uses the BsCCA algorithm to improve the recognition accuracy of high-frequency stimuli [19] and uses the dynamic window method to improve the ITR further.…”
Section: Methodsmentioning
confidence: 99%
“…During the experiment, the SNR of the EEG signal in the high-frequency part was lower than that in the low-frequency part, which decreased the recognition accuracy of high-frequency components of some subjects. The BsCCA algorithm proposed by Islam et al can improve the recognition accuracy of high-frequency stimuli [19]. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency that gives the maximum canonical correlation is recognized as the frequency of the target that the user is gazing at. This approach can be improved by applying a bank of bandpass filters [157,158]. Recent studies have pointed out that the nonuniform spectra of the spontaneous or background EEG can deteriorate the performances of the frequency recognition algorithm and have proposed efficient methods to achieve frequency recognition based on the effects of background EEG [159][160][161].…”
Section: Evoked Potentialsmentioning
confidence: 99%